Clinical Outcomes of Resorbable vs. Titanium Plates in Mandibular Fracture Fixation: A Prospective RCT - Rabia Naseer, Abdul Manan Shahid, Palwasha Ishaque, Zainab Khalid, Muhammad Azeem Khan, Amna Hassan, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A prospective randomized controlled trial compared clinical outcomes of resorbable versus titanium plate fixation in mandibular fractures among 100 adult patients (aged 18–60 years) with symphyseal or angle fractures